Optimization of Resveratrol Used as a Scaffold to Design Histone Deacetylase (HDAC-1 and HDAC-2) Inhibitors - Urias, Beatriz Silva [UNESP] (2022)
Histone deacetylases (HDAC) are epigenetic enzymes responsible for repressing gene expression through the deacetylation of histone lysine residues. Therefore, inhibition of HDACs has become an interesting approach for the treatment of several diseases, including cancer, hematology, neurodegenerative, immune diseases, bacterial infections, and more. Resveratrol (RVT) has pleiotropic effects, including pan-inhibition of HDAC isoforms; however, its ability to interfere with membranes requires additional optimization to eliminate nonspecific and off-target effects. Thus, to explore RVT as a scaffold, we designed a series of novel HDAC-1 and -2 inhibitors containing the 2-aminobenzamide subunit. Using molecular modeling, all compounds, except unsaturated compounds (4) and (7), exhibited a similar mode of interaction at the active sites of HDAC 1 and 2. The docking score values obtained from the study ranged from −12.780 to −10.967 Kcal/mol. All compounds were synthesized, with overall yields ranging from 33% to 67.3%. In an initial screening, compounds (4), (5), (7), and (20)–(26), showed enzymatic inhibitory effects ranging from 1 to 96% and 6 to 93% against HDAC-1 and HDAC-2, respectively. Compound (5), the most promising HDAC inhibitor in this series, was selected for IC50 assays, resulting in IC50 values of 0.44 µM and 0.37 µM against HDAC-1 and HDAC-2, respectively. In a panel of selectivity against HDACs 3–11, compound (5) presented selectivity towards Class I, mainly HDAC-1, 2, and 3. All compounds exhibited suitable physicochemical and ADMET properties as determined using in silico simulations. In conclusion, the optimization of the RVT structure allows the design of selective HDAC inhibitors, mainly targeting HDAC-1 and HDAC-2 isoforms.